2021
DOI: 10.3390/quat4030027
|View full text |Cite
|
Sign up to set email alerts
|

Climate on the Blanca Massif, Sangre de Cristo Mountains, Colorado, USA, during the Last Glacial Maximum

Abstract: Temperature-index modeling is used to determine the magnitude of temperature depression on the Blanca Massif, Colorado, required to maintain steady-state mass balances of nine reconstructed glaciers at their extent during the Last Glacial Maximum (LGM). The mean temperature depression thus determined is ~8.6 +0.7/−0.9 °C where the uncertainties account for those inherent in the glacier reconstructions, in model parameters (e.g., melt factors), and possible modest changes in LGM precipitation. Associated equili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…In the simulation designated “PR Low T,” we used daily air temperatures lowered uniformly by 7°C to simulate the effect of Last Glacial Maximum (LGM) temperature depression; however, for simplicity, we used measured precipitation as input for soil moisture recharge, as in the PR simulation. This amount of temperature depression was chosen because it is between the preferred temperature depressions derived from glacial mass balance modeling in the nearby Sangre de Cristo mountains (∼5°C: Leonard et al., 2017; ∼9°C: Brugger et al., 2021). In the simulation designated “MR Low T,” we used 7°C lower daily air temperature and modern precipitation but instead used the degree day snowmelt model to simulate snowpack and melt as input for soil moisture recharge in HYDRUS 1‐D.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the simulation designated “PR Low T,” we used daily air temperatures lowered uniformly by 7°C to simulate the effect of Last Glacial Maximum (LGM) temperature depression; however, for simplicity, we used measured precipitation as input for soil moisture recharge, as in the PR simulation. This amount of temperature depression was chosen because it is between the preferred temperature depressions derived from glacial mass balance modeling in the nearby Sangre de Cristo mountains (∼5°C: Leonard et al., 2017; ∼9°C: Brugger et al., 2021). In the simulation designated “MR Low T,” we used 7°C lower daily air temperature and modern precipitation but instead used the degree day snowmelt model to simulate snowpack and melt as input for soil moisture recharge in HYDRUS 1‐D.…”
Section: Resultsmentioning
confidence: 99%
“…Abundant paleoclimate evidence, reconstructed using mountain glacier, lake sediment, pollen and vegetation records, as well as paleoclimate modeling, indicate that the late Pleistocene was dramatically cooler than Holocene and present‐day conditions in western North America (Lora et al., 2017; Osman et al., 2021; Oster et al., 2015). For the southern Rocky Mountains just north of the study area, records of mountain glaciation coupled with glacier mass balance modeling indicate 5–9°C lower mean annual temperature during the LGM interval between ∼19 and 26 ka (Brugger et al., 2019, 2021; Dühnforth & Anderson, 2011; Leonard et al., 2017). This contrasts with the comparison of T (∆ 47 ) results between late Pleistocene samples and Holocene samples in our study sites, which show only ∼2°C lower glacial site average soil carbonate accumulation temperatures compared to Holocene sites, with largely overlapping ranges (Figures 5–7; Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Mosquito Range, temperature depressions of approximately −7.5 to −8°C were required to maintain maximum ice extents during the last glacial (Brugger et al, 2019a). In the Sangre de Cristo to the south, Leonard et al (2017) and Brugger et al (2021) found Pinedale maximum glaciers required approximately −5 and −8.5°C temperature changes relative to present, respectively-possibly underscoring the importance of 1). The data suggest variable initial deglaciation ages from maximum positions (i.e., normalized elevation and length = 1), followed by relatively consistent regional retreat to less than 20% maximum lengths and to high elevations by ca.…”
Section: Glacier Model Paleoclimate Interpretationsmentioning
confidence: 98%
“…These studies broadly indicate that mountain glaciers in Colorado reached their maximum extents near the end of or shortly after the global last glacial maximum (LGM; 19.0–26.5 ka; Clark et al, 2009) followed by several thousand years of punctuated deglaciation, and, in some cases, minor re-advances, which is similar to results from other parts of the Rocky Mountains (e.g., Licciardi and Pierce, 2008, 2018; Quirk et al, 2020, 2022) and western North America (Laabs et al, 2020, and references therein). The glacier climate reconstructions available for the Rocky Mountains of Colorado (Brugger, 2010, 2019a, b; Leonard et al, 2017; Brugger et al, 2021) generally suggest temperature depressions of 7–9°C colder than present and only modest changes in precipitation. However, compared to other ranges in the Colorado Rocky Mountains, the Elk Range (Fig.…”
Section: Introductionmentioning
confidence: 99%